Construction and phenotypic analysis of Kluyveromyces marxianus CCT 7735 recombinant flocculent strains for bioethanol production - Durán Meneses, Maria Fernanda (2015)
Flocculent yeasts are used in industrial processes because is a simple and cost-effective strategy for cell recovery from fermentation mash. However, yeast only shows natural flocculent phenotype in extreme conditions, which makes it a complex phenotype. Here, we describe the construction of novel Kluyveromyces marxianus CCT 7735 strains expressing constitutive flocculent phenotype by linear DNA integration of FLO1, FLO5, FLO9 and FLO10 genes from Saccharomyces cerevisiae BY4700. All recombinant strains showed flocculation ability at 40°C and 45°C, K. marxianus CCT 7735 FLO1 and FLO9 strains showed similar ethanol production profile when compared to K. marxianus CCT 7735 wild type. These novel strains have special flocculent characteristics that provide an advantage over wild type for use in continuous ethanol fermentation systems at high temperatures.